Longitudinal associations among maternal communication and adolescent posttraumatic stress symptoms after cancer diagnosis. Issue 7 (27th July 2015) - Murphy, Lexa K.; Rodriguez, Erin M.; Schwartz, Laura; Bemis, Heather; Desjardins, Leandra; Gerhardt, Cynthia A.; Vannatta, Kathryn; Saylor, Megan; Compas, Bruce E.
Abstract: Objective: The purpose of this study was to prospectively examine adolescent and maternal posttraumatic stress symptoms (PTSS) and maternal communication from time near cancer diagnosis to 12‐month follow‐up to identify potential risk factors for adolescent PTSS. Methods: Forty‐one adolescents with cancer (10–17 years, 54% female) and their mothers self‐reported PTSS at T1 (two months after cancer diagnosis) and T3 (1‐year follow‐up). At T2 (3 months after T1), mother–adolescent dyads were videotaped discussing cancer, and maternal communication was coded with macro (harsh and withdrawn) and micro (solicits and validations) systems. Results: Adolescent PTSS at T1 was associated with adolescent PTSS at T3. Greater maternal PTSS at T1 predicted greater harsh maternal communication at T2. There was an indirect effect of maternal PTSS at T1 on adolescent PTSS at T3 through maternal validations at T2. Conclusions: Findings underscore the importance of maternal PTSS, maternal communication, and subsequent adolescent PTSS over the course of treatment of childhood cancer. Copyright © 2015 John Wiley & Sons, Ltd. Copyright © 2015 John Wiley & Sons, Ltd.